Social support and coping among female foreign domestic helpers experiencing abuse and exploitation in Hong Kong - Choy, Chin Yung; Chang, Leanne; Man, Po Yee (Frontiers in Communication, 2022)
Introduction In Hong Kong, female foreign domestic workers are hired to assist with household chores and care. This study examined the coping and support-seeking strategies that the workers use to tackle workplace abuse and exploitation within the structural confines of their employment. Methods A mixed-method design that incorporated a face-to-face survey with 106 migrant domestic workers and 21 in-depth interviews was adopted. Results and discussion The results showed that most participants experienced some form of abuse or exploitation. Verbal threats and time exploitation were the most common forms of abuse and exploitation, respectively. Participants' marginalized group status muted their voices when workplace hazards occurred. Accordingly, they preferred emotion-based coping over problem-based coping when encountering abuse and exploitation. Their focus on emotional management was reflected in their acceptance of workplace conflicts as taken-for-granted norms, their avoidance of communicating with employers, and their nonconfrontational endurance of adverse working conditions. Aligned with participants' focus on emotion management, they also reported a stronger need for emotional support than other support functions. Their major sources of emotional support were religious beliefs and other migrant domestic workers in Hong Kong. Employers had the potential to fulfill the workers' support needs, but they must take the initiative due to imbalanced power relations.